MODEL HUBUNGAN ANTARA JUMLAH PENDUDUK DENGAN LUAS LAHAN PERTANIAN DAN PERMUKIMAN (Studi Kasus DAS Cidanau, Provinsi Banten) - Khursatul Munibah; Santun R P Sitorus; Ernan Rustiadi; Komarsa Gandasasmita; Hartrisari Hartrisari (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2019)
Increasing of population will effect to economic development that need the appropriation of lands for settlement, industry, infrastructure and service. Purposes of this research were to project population on 2018 and 2030; analyze land use change on period 2006-2018 and 2018-2030; analyze correlation between population with agriculture area and population with settlement area. Analysis of land use change was obtained by overlapping multitemporal land use maps. Regression approach was used to project population on 2018 and 2030; correlate between population with agriculture area and population with settlement area. The Result showed that 48% of villages which its population projection based on saturation model and 52% based on exponential model. Increasing rate of Agriculture area and settlement were 1,48%/12 years and 0,86%/12 years, respectively. Correlation between population with agriculture area were linier with R2 = 0, 7167 (2006); 0, 6343 (2018) and 0, 5082 (2030). Correlation between population with settlement were linier with R2 = 0, 7168 (2006); 0, 7312 (2018) and 0,568 (2030). Dynamical of R2 values showed contributory influence of population factor in increasing of agriculture area and settlement area.